HAKIKAT ILMU DALAM PANDANGAN ARCHIE J. BAHM MEMBACA KEMBALI 'WHAT IS SCIENCE?' - Robby H. Abror (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
The nature of science, according to Bahm, is fully understood related to six components, i.e.: problems, attitude, method, activity, conclusions, and effects. At least this is no other than an effort to understand each essential component for an understanding of the nature of science. Bahm's message, it is important that everybody that aware of the problem as scientific (such as, could related to instruments from attitude and scientific method), therefore become scientific, even he or she yet related to it.